PENGARUH BACK MASSAGE TERHADAP MATERNAL DEPRESSIVE SYMPTOMS PADA IBU POSTPARTUM - Anis Eka Pratiwi; Mohammad Anwar; Herlin Fitriana; Hestri Norhapifah (Jurnal Medika : Karya Ilmiah Kesehatan, 2017)
The postpartum period is a process of adaptation to physical and psychological changes. Postpartum mothers at risk for psychological disorders. Giving intervention such as back massage can be done by health workers to reduce maternal depressive symptoms. The aim of this study is to determine the effect of back massage to change maternal depressive symptoms score in postpartum. A Quasy experimental study of pretest-posttest with Non-equivalent control group design was undertaken among all postpartum in Sakina Idaman and Amanda hospital. The sampling technique used consecutive sampling with a sample 26 for each group. Back massage was given 2 times a week within a period of 4 weeks duration 15 minutes. Instruments Edinburgh Postnatal Depression Scale (EPDS) was used to measure maternal depressive symptoms in pretest-posttest. Sarason’s Social Support Questionnaire (SSQ) measured social support. The statistical test used paired t-test and independent t-test. Score of maternal depressive symptoms before and after intervention is similar 12,9±3,99 between 2 groups. The score significantly decrease after intervention (fourth week) 6,46±1,60 for intervention group and 8,73±1,63 for control group. Delta mean is 2,26 (Pvalue 0,04 CI 95% 0,05-4,47).